Major Development Mechanisms for the Infrastructure of the Transport and Logistics Complex in Kazakhstan - SAKTAGANOVA, Gulmira Sovetovna; LEGOSTAEVA, Lyubov Valentinovna; KARIPOVA, Ainur Tursynbaevna (Journal of Advanced Research in Law and Economics; Vol 9 No 4 (2018): JARLE Volume IX Issue 4(34) Summer 2018DO - 10.14505//jarle.v9.4(34).34, 2018)
The transport and logistics complex of Kazakhstan, international transport corridors and bridges provide a linkage in the formation of the Eurasian transcontinental bridge and ensuring the sustainable development of Kazakhstan. A modern transport and logistics system provides a highly efficient transport network within the country, an increase in cargo traffic in the territory of Kazakhstan, coordination of all modes of transport, development of the local transport infrastructure in the regions and integration of Kazakhstan transport infrastructure into the global transport system. Currently, the logistics sector has accumulated a set of problems. This problem concerns the technical and technological modernization of the transport system, which implies the reequipment of transport fleet and, accordingly, the technical and technological improvement of transport infrastructure. Kazakhstan adopts the experience of foreign countries, which use innovative transport technologies. Innovative technologies allow reducing transport costs and expanding regional cooperation. Kazakhstan has implemented an effective satellite tracking and monitoring system of transport and the latest information technologies. Kazakhstan cooperates with China in the field of transport and logistics, and develops transport and transit infrastructure, which makes it possible to service cargo flows with Europe. According to the Government Program of Development and Integration of Transport System Infrastructure until 2020, Kazakhstan attaches great importance to the development and renewal of rail, road, air, and water transport. Therefore, we propose to implement a set of measures aimed at developing the infrastructure of the transport and logistics complex in Kazakhstan. It is necessary to reequip the transport fleet, improve the technical and technological characteristics of transport infrastructure, develop multimodal transport technologies and improve roadside service. Based on public-private partnership, it is necessary to form a fund that would support the development of the national transport and logistics complex, the growth of transit traffic and the growth of tourism in the country. We propose to develop transit transport, logistics enterprises, logistics centers, warehouses, to implement national standards for logistics services. The United Transport and Logistics Company of Kazakhstan is required to establish a unified platform for transport and logistics services both in Kazakhstan and abroad. Such a company will provide data on transport routes, which will allow a client to choose the fastest route, improve the service of logistic services and shorten the delivery time, cost, safety and stability of cargo.